2006
DOI: 10.1103/physrevb.74.012407
|View full text |Cite
|
Sign up to set email alerts
|

Spin-liquid phase in an anisotropic triangular-lattice Heisenberg model: Exact diagonalization and density-matrix renormalization group calculations

Abstract: Based on exact diagonalization and density matrix renormalization group method, we show that an anisotropic triangular lattice Heisenberg spin model has three distinct quantum phases. In particular, a spin-liquid phase is present in the weak interchain coupling regime, which is characterized by an anisotropic spin structure factor with an exponential-decay spin correlator along the weaker coupling direction, consistent with the Cs 2 CuCl 4 compounds. In the obtained phase diagram, the spin-liquid phase is foun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
133
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(141 citation statements)
references
References 32 publications
7
133
0
1
Order By: Relevance
“…At zero field, there is already considerable work on the spatially anisotropic Heisenberg model in two dimensions 10,[40][41][42][43][44][45] . Away from the quasi-1d region, i.e.…”
Section: Low Field Regimementioning
confidence: 99%
“…At zero field, there is already considerable work on the spatially anisotropic Heisenberg model in two dimensions 10,[40][41][42][43][44][45] . Away from the quasi-1d region, i.e.…”
Section: Low Field Regimementioning
confidence: 99%
“…Theoretically, QSLs have been sought in spin-1/2 antiferromagnets with frustrated and/or competing interactions on triangular [28][29][30][31] , honeycomb [32][33][34][35][36] , square [37][38][39] , and kagomé [40][41][42][43][44] lattices. Amongst all these, the kagomé Heisenberg model (KHM) appears to possess the most robust QSL phase, and the only one consistently found in unbiased density matrix renormalization group (DMRG) calculations.…”
Section: Introductionmentioning
confidence: 99%
“…However, later numerical work [52] has shown that the ground state has "120 • order"-a special case of spiral order, discussed below, with an ordering wave vector Q = (2π/3,2π/3). A range of other methods have been used to study the Heisenberg model on the anisotropic triangular lattice including linear spin-wave theory [53,54], modified spin-wave theory [55], series expansions [12,56], the coupled cluster method [57], large-N expansions [58], variational Monte Carlo [59], resonating valence bond theory [15,19,[60][61][62], pseudofermion functional renormalization group [63], slave rotor theory [64], renormalization group [65], and the density matrix renormalization group [66]. These calculations show that for small J /J , Néel (π,π) order is realised and spiral (q,q) long-range AFM order is realized for J /J ∼ 1.…”
Section: Introductionmentioning
confidence: 99%